Elsevier's integrated genetics - Adkison, Linda R. (Mosby/Elsevier, 2007)
The book explains the morphologic variation observed in embryologic development and anatomic presentation. It provides susceptibility to infection and diseases. It offers insight into neurologic nad behaviorial abnormalities. It provides possibilities of gene therapy and pharmacogenomics.